Cognitive and Affective-Motivational Factors as Predictors of Students’ Home Learning During the School Lockdown - Lockl, Kathrin; Attig, Manja; Nusser, Lena; Wolter, Ilka (Frontiers in Psychology, 2021)
During the COVID-19 pandemic students were facing great challenges. Learning was shifted from the classroom to the home of the students. This implied that students had to complete their tasks in a more autonomous way than during regular lessons. As students’ ability to handle such challenges might depend on certain cognitive and motivational prerequisites as well as individual learning conditions, the present study investigates students' cognitive competencies as well as affective-motivational factors as possible predictors of coping with this new learning situation at home. The study uses data of Starting Cohort 2 of the German National Educational Panel Study (NEPS). Data of two measurement points are analyzed: Predictors were assessed at the earlier time point, when students (N = 1,452; Mage = 12 years, 8 months; 53.4% female) mostly attended seventh grade of a secondary school. They completed competence tests in reading as well as mathematics and rated affective-motivational aspects in terms of willingness to exert effort, learning enjoyment and intrinsic motivation. One and a half years later − during the COVID-19 pandemic and the first period of school closures − the second measurement point took place. Students’ parents rated the situation of learning at home with respect to students’ coping with the new situation and parents’ difficulties to motivate them. Regression analyses controlling for school track, students’ gender, and parents’ educational level and parental stress revealed that students’ reading competencies and their willingness to exert effort were significant predictors of their coping with the new learning situation at home. Moreover, parents reported that boys were more difficult to motivate to learn during this time as compared to girls. Other predictors (e.g., learning enjoyment) turned out to be non-significant when entered simultaneously in the regression analyses. The results point to the importance of children’s prerequisites for autonomous learning situations without structuring elements by teachers within the school context.